Potential of satellite data in catastrophic flood risk mapping and assessment: case studies from Asia and Africa - Amarnath, Giriraj; Rajah, Ameer; Alahacoon, Niranga; Inada, Yoshiaki; Inoue, R.; Aggarwal, Pramod K. (2014)
Over last decades, we have witnessed an upward global trend in natural disaster occurrence. Hydrological and meteorological disasters are the main contributors to this pattern. In 2011, hydrological disaster, such as floods and wet mass movements, represented 52% of the overall disaster reported, causing 139.8 million victims and more than U.S. $70 billion in damages. Remote sensing from space plays an important role in flood mapping and flood risk assessment. Satellite images acquired in both optical and microwave range of electro-magnetic emissions are utilized for solving many problems related to flood risk management. This paper presents two different research activities (1) flood detection algorithm which uses vegetation and water indices (NDVI, EVI, LSWI, DVEL) at a spatial resolution of 500m and time period 2000 – 2013 using MODIS Terra/Aqua and JAXA PALSAR satellite to spatially and temporally quantify flood inundation extent at a continental scale in South Asia, Southeast Asia and Nigeria in the context of emergency response and (2) blending satellite data and RADAR (Rapid Agriculture Disaster Assessment Routine) tool for rapid flood damage assessment in agriculture with a case study in Sri Lanka. The results of the present study will provide valuable information to flood policy makers and flood disaster researchers.